PENGARUH KEMAMPUAN BERPIKIR KRITIS DAN KEMAMPUAN PEMECAHAN MASALAH TERHADAP PERFORMA AKADEMIK SISWA SMK PROGRAM KEAHLIAN AKUNTANSI DAN KEUANGAN LEMBAGA - Olivia; Susilaningsih (PT Wahana Global Education, 2025)
this study aims to determine the effect of critical thinking skills and problem-solving skills on the academic performance of students in the accounting and finance program, both partially and simultaneously. Using a descriptive quantitative method, the data was analyzed using multiple regression analysis. The results showed that critical thinking skills partially had a significant effect on academic performance. Similarly, problem-solving skills show a significant partial effect. Simultaneously, both critical thinking and problem solving skills are proven to have a significant effect on the academic performance of students. This indicates that improving critical thinking and problem-solving skills is important to support the academic performance of accounting students.